PENGARUH KARAKTERISTIK INTERNAL DAN EKSTERNAL AUDITOR DALAM MEMBUAT KEPUTUSAN AUDIT BERBASIS ETIKA DENGAN PENDEKATAN MORAL COGNITIVE MENGGUNAKAN UJI PARTIAL LEAST SQUARE (PLS) - Yanto, Hary; DP, Emrinaldi Nur; Anggraini, Lila (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2013)
The objectives of This research are to analyze review and quality controlprocedures, auditor’s Locus of control, cognitive moral development,deontological and teleological moral evaluation that can affect the prematuresign off. And to test the presence of intervening variables deontological andteleological moral evaluation in direct and indirect relationships of cognitivemoral development of the termination behavior of audit procedures.While the sample of this research in the KAP auditors working in Pekanbaru,Padang, and Batam with 69 sample auditors. Methods of data collection in thisstudy is a survey method with a questionnaire instrument. Method of data analysisused to test the quality of the data that include validity, reliability testing, andhypothesis testing is the analysis of the structural equation model using softwareSmartPLS 2.0.M3.Hypothesis testing using partial least square test showed that the variables andquality control review procedures and locus of control significantly influenceauditors premature sign off, so giving impact to the reduction in the quality of theresulting audit report auditor. While the variable cognitive moral development,deontological and teleological moral evaluation does not directly affectpremature sign off. Cognitive moral development variables had a significantrelationship with the variable deontological and teleological moral evaluation.Value of R-Square indicates that the variables jointly review procedures andquality control, locus of control, cognitive moral development, deontological andteleological moral evaluation contribute to the dependent variable (prematuresign off) of 35.68%, while the remaining 64.32% is explained by other variablesoutside the research model.Keyword : premature sign off, review prosedure and quality control, locus ofcontrol, cognitive moral development, deontological and teleologicalmoral evaluation